A numerical method for designing topological superconductivity induced by s-wave pairing - Jingnan Hu; Aiyun Luo; Zhijun Wang; Jingyu Zou; Quansheng Wu; Gang Xu (npj Computational Materials)
Abstract Topological superconductors have garnered significant attention due to their potential for realizing topological quantum computation. However, a universal computational tool based on first-principles calculations for predicting topological superconductivity has not yet been fully developed, posing substantial challenges in identifying topological superconducting materials. In this paper, we present a numerical method to characterize the superconducting spectrum and topological invariants of two-dimensional (2D) slab systems using first-principles band structure, implemented in the open-source software WannierTools. To more accurately model the superconducting proximity effect, we integrate a phenomenological theory of SC pairing decay module into the program. Our approach can be applied to classical superconductor-topological insulator (SC-TI) heterostructures, SC-semiconductor heterostructures, and intrinsic topological superconductors. The program’s validity is demonstrated using the topological crystal insulator SnTe, the Rashba semiconductor InSb, and the superconductor NbSe2 as examples. We anticipate that this tool will accelerate the discovery of topological superconductor candidates.